MENGENAL KARAKTER MASYARAKAT JEPANG MELALUI KINESIK TOKOH UTAMA DORAMA â€œCHIBI MARUKO CHANâ€ : SUATU TINJAUAN SOSIOLINGUISTIK - Pipiet Furisari (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2016)
Kinesics, as non verbal and non linguistic means of communication, is used to achieve interaction perfection or communication support. Kinesics has close relation with language behaviour influenced by certain culture in certain community, in this case Japanese community. This study used qualitative approach aiming at describing child kinetics occuring through main character of â€œChibi Maruko Chanâ€ drama. The techniques of data colection are library research and observation. While the techniques of data analysis are observing the child kinesics used in the drama, classifying, analysing and interpreting the finding. The result showed that in â€œChibi Maruko Chanâ€ drama, its main character, Maruko, besides using child kinesics, she also used general kinesics, while slang kinesics was not used. The functions of kinesics mostly used are complement, substitution, and repetition. Based on the kinesics performed, Japanese community have several characteristics, they are expressive, adore shame culture, tolerant, â€žaijouâ€Ÿ, harmonious, like forgiving/thanking, respect the quality, â€žkoujoushinâ€Ÿ, and careful.Keywords:Character,culture, function, kinesics, non-verbal communication.